Domus aurea diálogos en la casa de Virgilio - Fernández Alba, Antonio, 1927- (Madrid : Biblioteca Nueva, 1998)
Theoretical dialogue between the poet, Virgil and the architect, Ictino.
Keywords: Architecture -- Philosophy; Architectural theory; Electronic books